Property rights and elites - Alice H. Amsden (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
An elite derives its status from its relationship to property, whether physical or human capital. While stable property rights are necessary for everyday business, unstable property rights that result in major institutional changes (such as land reform) may have a positive impact on economic development. When are the 'wrong' property rights right? Institutional changes have a positive impact on economic development when a country's elite can manage them. To support this generalization we examine the managerial capacity associated with elite status, highlighting which capabilities enable them to control changes in property rights regimes to their individual and national advantage. We compare how nationalization of foreign firms, a radical change in property rights, was managed in Argentina, China, Korea and Taiwan after the Second World War.
Keywords: A1; F0; J0; L0; 330; Elites; property rights; indigensim; capabilities; role models; Eigentumsrecht; Elite; Entwicklung; Institutioneller Wandel